A auditoria independente no contexto da governança corporativa - Barros, José da Silva (2009)
The Independent Audit is considered a relevant agent of corporate governance, because its main target is to verify if the financial statements prepared and disclosed to the stakeholders properly reflect the reality of the company. Having corporate governance and independent audit as bases of this study, the problem question consists on the verification of which is the level of participation and contribution of the independent audit in the context of corporate governance, in relation to the adoption of the good practices current in governance literature, in the conception of the auditors. Therefore, this study has the objective of analyze, in the vision of those professionals, how much the independent audit participates and contributes for the process of empowerment of the practices of corporate governance in the companies listed in Differentiated Levels 1 and 2 and in the New Market of Bovespa. The reasons for the realization of this study consist on providing to the academic, professional and enterprise community knowledge about the vision of the independent auditor and its effective participation and contribution to the empowerment of the good practices, as a governance agent. More over, the assumed prerequisite the idea of the research is that the auditors realize their performance in the context of corporate governance, and agree that they contribute for the adoption of the best practices in the companies, forming itself, therefore, as indispensable agent to provide the credibility of the information disclosed to the market. For the reach of the objectives, it was made an exploratory research with qualitative approach, whose instruments of investigations collect were bibliographical, documentary and a questionnaire applied to the independent auditors responsible by the financial statements of the previously characterized companies. The result demonstrated that the practices mentioned in the collect instrument are conform and are adopted by the audited companies. Is still concluded that, in the vision of the independent auditors, the audit contributes for the empowerment of the practices of corporate governance in the audited companies, considering the participation of the auditors in the adjustment of the investigated practices.